Building the Isan Long Drum for study the sound quality of Isan long drum - Petsaen, Jakkrapong (Journal of Music and Performing Arts Khon Kaen University, 2023)
Originally, Isan long drums were created by people living in the community. It was public property. It was used as a musical instrument in ceremonial activities of people in the village by using material, equipment or tools which could be found locally. The creating area was a certain center such as temples or halls. The creating knowledge by from carpentry and applied the shape from storytelling or imagination of people in the community to acquire the shape of Northeastern long drums as they wanted. Building the Isan Long Drum for study the sound quality of Isan long drum had the objective to study development of sound quality of Isan long drums by using qualitative research process. The study was from the data of various media and from interview and the data were analyzed to create Isan long drums. The researcher has developed, improved on material and equipment used in producing Isan long drums so that it would be consistent with the current social context such as aesthetics, advancement, convenience, light weight and endurability. From the test of Isan long drums which used 3 types of wood including Burma padauk, Jackfruit wood and Raintree wood, to be used for quality research studies and further development of the Isan long drum.